SISTEM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KUALITAS CRUDE PALM OIL SEBAGAI BAHAN BAKU MINYAK GORENG MENGGUNAKAN MATLAB DENGAN METODE FUZZY LOGIC TSUKAMOTO - Nirwan Sinuhaji; Raheliya Ginting; Benar; Cindy Lestiana (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
ABSTRACT The best decision is the main goal in a problem solving. The decision in det ermining the stock of Crude Palm Oil (CPO) in Palm Oil Mills (PMKS) is very important because it is directly related to the survival of the company. Solutions in solving problems in determining the best quality of CPO as raw material for cooking oil with the desired quality. By using Fuzzy Tsukamoto, it is easier for the processing department to determine the best quality of CPO. To determine the best quality of CPO, data on free fatty acids, water content, impurities and temperature are needed. Based on the tests that have been carried out, the quality of CPO with the input of free fatty acids = 0.7 FFA, water content = 0.23 Moisture, dirt content = 0.25 Dirty and temperature = 98oC in a decent condition, which is 39.48%. The results of the application system for determining the quality of oil palm seeds using the GUI Matlab are 23%, with a difference of 16.48%. In the Matlab application system that has been tested, if the free fatty acid is higher between 0.6-1 and the impurities content is high between 0.24-0.30 then the quality of the CPO produced is rancid. Meanwhile, if the free fatty acid is low between 0-0.3 and normal levels of impurities are between 0.18-0.26, then the quality of CPO is not feasible. More about this source textSource text required for additional translation information Send feedback Side panels